Casting powder for continuous casting of high-carbon steel slab and continuous casting method
By introducing B2O3 and Na2O into the continuous casting protective slag of high-carbon steel slabs, combined with isopropyl trioleic acid acyloxytitanate, the defects of fluorine element pollution and traditional protective slag in high-pulse speed continuous casting are solved, and the defects of high-pulse speed continuous casting are achieved. Safe, environmentally friendly and high-quality casting production.
Patent Information
- Application Number
- CN202411530170.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-17
AI Technical Summary
The existing high-carbon steel slab continuous casting protective slag contains fluorine elements, which leads to environmental pollution and health threats. In traditional designs, low alkalinity and high viscosity protective slags have steel leakage and crack defects during high-pull speed continuous casting.
Develop a fluorine-free high-carbon steel slab continuous casting protective slag, which reduces the melting temperature by introducing B2O3, reduces the viscosity of Na2O, and uses isopropyl trioleic acid acyloxytitanate to promote the increase of crystallization species and inhibits the crystallization The precipitation of stone and wollastonite increases the precipitation of yellow feldspar and perovskite, and improves lubricating and heat transfer properties.
It realizes safe, non-toxic and environmentally friendly high alkaline protection slag, reduces the concentration of crystallization factor, inhibits cracks and steel leakage, improves the surface quality of the casting billet and the stability of continuous casting production, and avoids the use of fluorine environmental and health risks.
Smart Images

Figure CN119319224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal casting, and in particular to a protective slag for continuous casting of high carbon steel slabs and a continuous casting method. Background Art
[0002] During the continuous casting of high carbon steel slabs, mold slag plays multiple key roles. It insulates heat by forming a slag layer on the surface of the molten steel to reduce heat loss, while isolating the air to prevent oxidation of the molten steel and ensure the purity of the steel. The mold slag can also absorb inclusions, reduce the inclusion content in the ingot, and improve the quality of steel. In addition, the slag film it forms between the wall of the crystallizer and the solidified shell acts as a lubricant, reduces the resistance to billet drawing, and prevents the ingot shell from sticking to the crystallizer. The filling effect of the mold slag also helps to improve the heat transfer efficiency of the crystallizer, make the solidification of the ingot more uniform, and reduce internal defects. The performance requirements of the mold slag include suitable melting temperature, good wettability, appropriate viscosity and slag film distribution, and good heat transfer performance. For example, a mold slag with a lower melting temperature and viscosity, as well as a higher proportion of the slag film liquid layer, helps reduce defects such as bonding, leaking and cracks, and ensures a smooth continuous casting process. The improvement of environmental protection requirements has led to the development of fluorine-free or low-fluorine mold slags. These new mold slags use alternatives such as TiO2, which are both environmentally friendly and efficient. They show good effects in melting characteristics, lubrication performance, slag film structure and heat transfer characteristics, meet the process requirements of continuous casting production in factories, and have achieved good application results. With the deepening of research, future mold slag will pay more attention to high efficiency and environmental protection to meet the sustainable development needs of the steel industry.
[0003] CN117206481A belongs to the field of metal continuous casting technology, specifically a protective slag for high-carbon steel square billet high-speed continuous casting and its preparation method and application. The protective slag design breaks through the design idea of low basicity and high viscosity of traditional high-carbon steel protective slag, takes into account the improvement of lubrication and control of heat transfer, and has the advantages of high consumption, high melting rate, low melting point, low viscosity and suitable crystallization ability. It improves the crystallization ability, enhances the control of heat transfer of the crystallizer under high pulling speed, inhibits cracks, reduces viscosity and melting point, increases the consumption of protective slag, enhances lubrication ability, reduces carbon content, increases melting rate, and ensures the supply of liquid slag under high pulling speed. Pre-melting material is used to ensure the stability of protective slag composition and application process performance. Therefore, after application in the high-speed continuous casting process of high-carbon steel, no steel leakage alarm and slag ring phenomenon occur, the continuous casting process is stable, and the quality of the ingot is good, which provides a guarantee for the stable continuous casting production and promotion of high-speed high-carbon steel.
[0004] CN103722142A discloses a boron-containing low-fluorine protective slag for medium carbon steel, the chemical composition of the protective slag is as follows by mass percentage: CaO38~43%, SiO230~35%, Al2O32~5%, MgO1~3%, (Na2O+Li2O)10~15%, B2O36~11%, CaF22~5%, that is, CaO and SiO2 are used as base materials, and Na2O, Al2O3, CaF2, MgO and the like are added as flux. The low-fluorine protective slag used in the invention has excellent crystallization performance, uniform and stable heat transfer, and good lubrication and melting properties, and can effectively reduce surface defects such as longitudinal cracks; in particular, boron is used instead of fluoride, and calcium borosilicate (Ca2O3) is used to precipitate the boron-containing mineral phase. 11 Si4B2O 22 ) can replace lanceolite and reduce the fluoride content in the protective slag, which is beneficial to environmental protection; at the same time, the discovery of new lanceolite substitutes can create considerable economic and social benefits.
[0005] Currently, many mold slags contain fluorine in different proportions. Fluorine and its compounds are usually toxic, which may cause problems during the use of mold slag. Some fluorine will be released into the environment in the form of gas, while other parts may adhere to the slag coating and then enter the cooling water and steel rolling system. This will not only corrode the equipment, but also pose a threat to human health, eventually leading to air and water pollution, and even destroying the ozone layer, becoming one of the sources of environmental pollution. Therefore, the development of fluorine-free mold slag is an important direction for future research and development. Summary of the invention
[0006] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide a protective slag for continuous casting of high carbon steel slabs and a continuous casting method.
[0007] The melting temperature, viscosity and other macroscopic properties of the protective slag are closely related to its chemical composition, so the determination of the composition of the protective slag is the basis for the development of the protective slag. The improvement of environmental protection requirements has prompted the development of fluorine-free or low-fluorine protective slags. Therefore, a fluorine-free protective slag for continuous casting of high-carbon steel slabs is prepared in the present invention. By introducing B2O3, the melting temperature can be reduced, and the presence of Na2O can reduce the viscosity of the slag. In addition, B2O3 and Na2O can change the transition temperature to a certain extent, and the transition temperature will greatly affect the melt structure of the protective slag and control its solidification and crystallization behavior. The protective slag prepared by the present invention avoids the use of fluorine, is not only safe and non-toxic but also more environmentally friendly. Through the reasonable effects of various formulas, a protective slag for continuous casting of high-carbon steel slabs with high basicity and non-toxic and harmless is obtained. In addition, the added isopropyl trioleyl titanate can not only closely connect the various components, thereby causing the protective slag to be filled more densely when melted, but the titanium dioxide in the isopropyl trioleyl titanate promotes the increase of crystallization types, inhibits the precipitation of lanceolite and wollastonite in the protective slag, and promotes the precipitation of pyroxene and perovskite. The precipitation of these complex compounds plays a good role in thermal insulation in the protective slag, reduces the concentration of crystallization factors in the protective slag, inhibits the occurrence of crystallization, and achieves the effect of improving lubrication while maintaining the stability of the heat flow of the slag film. TiO2 can reduce viscosity, and at the same time, it can obtain good heat transfer performance and improve the glass properties of the slag while taking into account the lubrication of the ingot.
[0008] To achieve the above object, the present invention provides a protective slag for continuous casting of high carbon steel slabs, comprising the following components in parts by weight: 15-50 parts of premelt, 10-30 parts of wollastonite, 3-10 parts of quartz, 3-8 parts of albite, 2-5 parts of magnesia, 2-4 parts of borax, 10-15 parts of soda ash, 1-3 parts of lithium carbonate, 1-2 parts of bentonite, 4-8 parts of graphite, 1-3 parts of adhesive, 1-4 parts of isopropyl trioleyl titanate, and its effective chemical components are: In terms of mass percentage, they are: CaO: 22.5~30.5%, SiO2: 35.0~50.5%, MgO: 2~6.5%, Fe2O3: ≤2.0%, Al2O3: 3~7.15%, Na2O: 8~15.5%, Li2O: 0.3~1.5%, B2O3: 0.3~1.1%, TiO2: 0.1~1%, fixed carbon: 3.0~6.0%, and the rest are unavoidable impurities.
[0009] Furthermore, the premelt is prepared by adding soda ash, limestone, albite, dolomite and coke into a premelting furnace and burning to obtain a liquid material, which is then cooled by cold water and the chemical composition is detected to be CaO: 35~36%, SiO2: 32~35%, Al2O3≤3.0%, MgO≤3.0%, MnO≤1.0%, Na2O: 7~8%, and the rest are unavoidable impurities.
[0010] Furthermore, the basicity of the protective slag is 0.65-1.0, the melting point is 950-1100° C., the melting speed is 15-35 s, and the viscosity is 0.1-0.3 Pa·s at 1300° C.
[0011] Furthermore, the adhesive is a mixture of sodium carboxymethyl cellulose and yellow dextrin in a mass ratio of (1-3): (2-4).
[0012] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps: S1. Weigh each component in the formula according to the proportion and stir evenly to obtain a mixture, add water to make a slurry, and then stir and grind to obtain a slurry; S2. The slurry is filtered, spray granulated and then sieved to obtain the product.
[0013] Furthermore, the slurry concentration is 55-65wt%.
[0014] Furthermore, the grinding time is 60 to 90 minutes.
[0015] Furthermore, the conditions for the spray granulation are: tower temperature 650-750° C., tower outlet temperature 160-180° C., and pump pressure 1.3-2.3 MPa.
[0016] Furthermore, the particle size of the screening is that the screening screen is a double-layer screen with an upper layer of 18 mesh and a lower layer of 60 mesh.
[0017] Beneficial effects of the present invention: 1. Compared with the prior art, the protective slag prepared by the present invention avoids the use of fluorine, is not only safe and non-toxic but also more environmentally friendly. Through the reasonable effects of various formulas, a protective slag for continuous casting of high-carbon steel slabs with high basicity and non-toxic and harmless is obtained. In addition, the added isopropyl trioleyl titanate can not only closely connect the various components, thereby causing the protective slag to be filled more densely when melted, but the titanium dioxide in the isopropyl trioleyl titanate promotes the increase of crystallization types and the reduction of viscosity, and at the same time, it can obtain good heat transfer performance and improve the glass properties of the slag while taking into account the lubrication of the cast billet.
[0018] 2. In the present invention, a fluorine-free protective slag for continuous casting of high-carbon steel slabs is prepared. By introducing B2O3, the melting temperature can be reduced, and the presence of Na2O can reduce the viscosity of the slag. In addition, B2O3 and Na2O can change the transition temperature to a certain extent, and the transition temperature will greatly affect the melt structure of the protective slag and control its solidification and crystallization behavior. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a photo of the protective slag sample prepared by the present invention. DETAILED DESCRIPTION
[0020] The protective slag for continuous casting of high carbon steel slabs in the present invention comprises the following components: premelt, wollastonite, quartz, albite, magnesia, borax, soda ash, lithium carbonate, bentonite, graphite, adhesive, isopropyl trioleyl titanate, wherein the premelt is the main component of the protective slag, usually composed of a variety of compounds, and can be melted at a lower temperature to form a liquid slag film, which plays a role in lubrication and heat transfer control. Quartz helps to increase the melting temperature and viscosity of the protective slag, and has a certain structural stability at high temperature, which helps to form a uniform slag film. Sodium feldspar can reduce the melting point of the protective slag, promote its melting, and provide a certain alkaline environment, which helps to absorb and dissolve inclusions in molten steel. Magnesia can reduce the transition temperature, improve the lubrication ability of the slag film, and reduce the risk of bonding. Borax helps to reduce the melting point and viscosity of the protective slag, improve its flow performance, and has a certain lubricating effect at high temperature. Soda ash can improve the melting performance of the protective slag, reduce the melting temperature of the protective slag, and improve the ability to form a slag quickly. Lithium carbonate can reduce the melting temperature and viscosity of the protective slag, and at the same time, it helps to form a uniform slag film at high temperatures and improve its lubrication properties. Graphite, as a carbon source, constitutes the protective slag skeleton structure, which helps to adjust the melting properties and lubrication properties of the protective slag, and at the same time has a certain antioxidant effect at high temperatures. The adhesive is used in the granulation process of the protective slag, which helps to improve the particle strength and stability of the protective slag, and is convenient for storage and use. Isopropyl trioleyl titanate not only helps to improve the melting properties and slag film formation of the protective slag, but is also responsible for providing titanium dioxide, thereby achieving the effect of improving lubrication while maintaining the control of the heat flow of the slag film. These components work together to ensure that the protective slag can effectively prevent the oxidation of molten steel, absorb inclusions, lubricate the ingot, insulate and improve the heat transfer of the crystallizer during the continuous casting process, thereby improving the surface quality of the ingot and the stability of continuous casting production. Example 1
[0021] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain liquid material, and then cool them down with cold water to obtain premelting material. Detect the chemical composition to find CaO: 35.56%, SiO2: 33.65%, Al2O3: 0.52%, MgO: 0.78%, MnO: 0.66%, Na2O: 7.44%, and the rest are inevitable impurities; add 20 parts of premelting material, 28 parts of wollastonite, 7 parts of quartz, 4 parts of albite, 3 parts of magnesia, 3 parts of borax, 14 parts of soda ash, 2 parts of lithium carbonate, 1 part of bentonite, 7 parts of graphite, sodium carboxymethyl cellulose and yellow dextrin by weight. 2 parts of adhesive and 2 parts of isopropyl trioleyl titanate are mixed in a ratio of 3:2, and the effective chemical components are as follows by mass percentage: CaO: 28.3%, SiO2: 40.15%, MgO: 4.15%, Fe2O3: 0.46%, Al2O3: 4.67%, Na2O: 8.67%, Li2O: 0.69%, B2O3: 0.57%, TiO2: 0.33%, fixed carbon: 5.5%, and the rest are inevitable impurities. The components are stirred evenly to obtain a mixture, water is added to make a slurry, and then stirred and ground for 80 minutes to obtain a 65wt% slurry; S2. After the slurry is filtered, it is spray granulated at a tower temperature of 680°C, an outlet temperature of 170°C, and a pump pressure of 2.2MPa, and then sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh. Example 2
[0022] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain a liquid material, and then cool them down with cold water to obtain a premelting material. The chemical composition is detected to be CaO: 35.31%, SiO2: 32.42%, Al2O3: 0.83%, MgO: 0.65%, MnO: 0.45%, Na2O: 7.20%, and the rest are inevitable impurities; 25 parts of premelting material, 25 parts of wollastonite, 6 parts of quartz, 6 parts of albite, 4 parts of magnesia, 3 parts of borax, 12 parts of soda ash, 2 parts of lithium carbonate, 2 parts of bentonite, 5.7 parts of graphite, sodium carboxymethyl cellulose and yellow dextrin by weight. 2 parts of adhesive and 3 parts of isopropyl trioleyl titanate are mixed in a ratio of 3:2, and the effective chemical components are as follows by mass percentage: CaO: 27.55%, SiO2: 39.87%, MgO: 4.56%, Fe2O3: 0.53%, Al2O3: 5.21%, Na2O: 9.85%, Li2O: 0.67%, B2O3: 0.72%, TiO2: 0.41%, fixed carbon: 4.5%, and the rest are inevitable impurities. The components are stirred evenly to obtain a mixture, water is added to make a slurry, and then stirred and ground for 85 minutes to obtain a 62wt% slurry; S2. After the slurry is filtered, it is spray granulated at a tower temperature of 690°C, an outlet temperature of 167°C, and a pump pressure of 2.0 MPa, and then sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh. Example 3
[0023] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain a liquid material, and then cool them down with cold water to obtain a premelting material. The chemical composition is detected to be CaO: 35.76%, SiO2: 33.24%, Al2O3: 0.68%, MgO: 0.72%, MnO: 0.56%, Na2O: 7.68%, and the rest are inevitable impurities; 30 parts of premelting material, 20 parts of wollastonite, 5 parts of quartz, 5 parts of albite, 3 parts of magnesia, 2 parts of borax, 12 parts of soda ash, 3 parts of lithium carbonate, 1 part of bentonite, 5 parts of graphite, sodium carboxymethyl cellulose and yellow dextrin in a mass ratio; 3:2 mixed adhesive 2 parts, isopropyl trioleyl titanate 2 parts, its effective chemical composition by mass percentage is: CaO: 25.67%, SiO2: 41.23%, MgO: 4.56%, Fe2O3: 0.67%, Al2O3: 5.05%, Na2O: 10.32%, Li2O: 0.46%, B2O3: 0.56%, TiO2: 0.32%, fixed carbon: 4.0%, the rest are inevitable impurities, the components are stirred evenly to obtain a mixture, water is added to make pulp, and then stirred and ground for 85 minutes to obtain a 60wt% slurry; S2. After the slurry is filtered, it is sprayed and granulated at a tower temperature of 705°C, an outlet temperature of 172°C, and a pump pressure of 1.8MPa. Then it is sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh. Example 4
[0024] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain a liquid material, and then cool them down with cold water to obtain a premelting material. The chemical composition is detected to be CaO: 35.81%, SiO2: 32.23%, Al2O3: 0.34%, MgO: 0.46%, MnO: 0.52%, Na2O: 7.13%, and the rest are inevitable impurities; 34 parts of premelting material, 25 parts of wollastonite, 6 parts of quartz, 5 parts of albite, 3 parts of magnesia, 2 parts of borax, 10 parts of soda ash, 2 parts of lithium carbonate, 1 part of bentonite, 5.5 parts of graphite, sodium carboxymethyl cellulose and yellow dextrin by weight. 1 part of adhesive and 1 part of isopropyl trioleyl titanate after mixing in a ratio of 3:2, the effective chemical components of which are calculated by mass percentage as follows: CaO: 27.5%, SiO2: 42.12%, MgO: 4.81%, Fe2O3: 0.61%, Al2O3: 4.60%, Na2O: 9.02%, Li2O: 0.43%, B2O3: 0.36%, TiO2: 0.22%, fixed carbon: 4.2%, and the rest are inevitable impurities. The components are stirred evenly to obtain a mixture, water is added to make a slurry, and then stirred and ground for 75 minutes to obtain a 59wt% slurry; S2. After the slurry is filtered, it is spray granulated at a tower temperature of 720°C, an outlet temperature of 165°C, and a pump pressure of 1.8MPa, and then sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh. Example 5
[0025] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain liquid material, and then cool them down with cold water to obtain premelting material. Detect the chemical composition to find CaO: 35.23%, SiO2: 32.89%, Al2O3: 0.73%, MgO: 0.61%, MnO: 0.53%, Na2O: 7.35%, and the rest are inevitable impurities; add 20 parts of premelting material, 30 parts of wollastonite, 6 parts of quartz, 4 parts of albite, 5 parts of magnesia, 3 parts of borax, 10 parts of soda ash, 1 part of lithium carbonate, 1 part of bentonite, 7 parts of graphite, sodium carboxymethyl cellulose and yellow dextrin by weight. 3 parts of adhesive and 3 parts of isopropyl trioleyl titanate are mixed in a ratio of 3:2, and the effective chemical components are as follows by mass percentage: CaO: 26.56%, SiO2: 41.13%, MgO: 4.45%, Fe2O3: 0.71%, Al2O3: 5.12%, Na2O: 9.04%, Li2O: 0.61%, B2O3: 0.56%, TiO2: 0.42%, fixed carbon: 5.5%, and the rest are inevitable impurities. The components are stirred evenly to obtain a mixture, water is added to make a slurry, and then stirred and ground for 80 minutes to obtain a 57wt% slurry; S2. After the slurry is filtered, it is sprayed and granulated at a tower temperature of 730°C, an outlet temperature of 174°C, and a pump pressure of 1.6MPa. Then, it is sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh. Example 6
[0026] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain a liquid material, and then cool them down with cold water to obtain a premelting material. The chemical composition is detected to be CaO: 35.09%, SiO2: 33.34%, Al2O3: 0.58%, MgO: 0.72%, MnO: 0.81%, Na2O: 7.51%, and the rest are inevitable impurities; 17 parts of premelting material, 25 parts of wollastonite, 10 parts of quartz, 8 parts of albite, 5 parts of magnesia, 3 parts of borax, 12 parts of soda ash, 3 parts of lithium carbonate, 2 parts of bentonite, 7.5 parts of graphite, sodium carboxymethyl cellulose and yellow dextrin by weight. 3 parts of adhesive and 2 parts of isopropyl trioleyl titanate are mixed in a ratio of 3:2, and the effective chemical components are as follows by mass percentage: CaO: 28.01%, SiO2: 38.95%, MgO: 4.06%, Fe2O3: 0.67%, Al2O3: 5.03%, Na2O: 9.74%, Li2O: 0.56%, B2O3: 0.63%, TiO2: 0.31%, fixed carbon: 6.0%, and the rest are inevitable impurities. The components are stirred evenly to obtain a mixture, water is added to make a slurry, and then stirred and ground for 80 minutes to obtain a 61wt% slurry; S2. After the slurry is filtered, it is spray granulated at a tower temperature of 700°C, an outlet temperature of 175°C, and a pump pressure of 2.0 MPa, and then sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh.
[0027] Comparative Example 1
[0028] A method for preparing mold slag for continuous casting of high carbon steel slabs comprises the following steps, measured in parts by weight: S1. Add soda ash, limestone, albite, dolomite and coke into a premelting furnace, burn them to obtain a liquid material, and then cool them down with cold water to obtain a premelting material. The chemical composition is detected to be CaO: 35.03%, SiO2: 33.04%, Al2O3: 0.60%, MgO: 0.57%, MnO: 0.61%, Na2O: 7.56%, and the rest are inevitable impurities; 14 parts of premelting material, 26 parts of wollastonite, 10 parts of quartz, 8 parts of albite, 5 parts of magnesia, 3 parts of borax, 14 parts of soda ash, 3 parts of lithium carbonate, 2 parts of bentonite, 6 parts of graphite, and carboxylic acid. 3 parts of an adhesive prepared by mixing sodium methyl cellulose and yellow dextrin in a mass ratio of 3:2, wherein the effective chemical components are as follows by mass percentage: CaO: 28.05%, SiO2: 42.31%, MgO: 4.62%, Fe2O3: 0.45%, Al2O3: 5.02%, Na2O: 9.84%, Li2O: 0.44%, B2O3: 0.51%, fixed carbon: 4.8%, and the rest are inevitable impurities. The components are uniformly stirred to obtain a mixture, water is added to prepare a slurry, and then stirred and ground for 80 minutes to obtain a 60wt% slurry; S2. After the slurry is filtered, it is spray granulated at a tower temperature of 700°C, an outlet temperature of 170°C, and a pump pressure of 1.8MPa, and then sieved on a double-layer sieve with an upper layer of 18 mesh and a lower layer of 60 mesh.
[0029] Test Example 1
[0030] The physical and chemical performance indicators of the high carbon steel slab continuous casting mold slag prepared in the embodiment and the control example were tested, and the specific results are shown in Table 1.
[0031] Table 1 Physical and chemical properties of high carbon steel slab continuous casting mold slag Experimental protocol Alkalinity Melting point / ℃ Viscosity at 1300℃ / Pa·s Melting speed / s Example 1 0.74 1056 0.19 23 Example 2 0.78 1043 0.15 25 Example 3 0.84 1035 0.14 27 Example 4 0.82 1028 0.21 31 Example 5 0.79 1041 0.16 28 Example 6 0.87 1035 0.18 25 Comparative Example 1 0.89 1062 0.28 34 The high carbon steel slab continuous casting protection slag prepared by the present invention has various performance and parameters such as melting point, viscosity, melting speed and basicity, which meet the requirements, so it can inhibit the generation of surface cracks on the casting slab; at the same time, the protection slag of the present invention avoids the use of fluorine, which not only reduces the corrosion of equipment, but also does not pollute the environment. Various components work together to ensure that the protection slag can effectively prevent the oxidation of molten steel, absorb inclusions, lubricate the casting slab, insulate and heat-preserve, and improve the heat transfer of the crystallizer during the continuous casting process, thereby improving the surface quality of the casting slab and the stability of continuous casting production.
[0032] The present invention provides a fluorine-free protective slag for continuous casting of high-carbon steel slabs. By introducing B2O3, the melting temperature can be reduced, and the presence of Na2O can reduce the viscosity of the slag. In addition, B2O3 and Na2O can change the transition temperature to a certain extent, and the transition temperature will greatly affect the melt structure of the protective slag and control its solidification and crystallization behavior. The protective slag prepared by the present invention avoids the use of fluorine, is not only safe and non-toxic but also more environmentally friendly. Through the reasonable effects of various formulas, a protective slag for continuous casting of high-carbon steel slabs with high basicity and non-toxic and harmless is obtained. In addition, the added isopropyl trioleyl titanate can not only tightly connect the various components, thereby causing the protective slag to be filled more densely when melted, but the titanium dioxide in the isopropyl trioleyl titanate promotes the increase of crystallization types, inhibits the precipitation of lanceolite and wollastonite in the protective slag, and promotes the precipitation of pyrophyllite and perovskite. The precipitation of these complex compounds plays a good role in heat insulation in the mold slag, reduces the concentration of crystallization factors in the mold slag, inhibits its crystallization, and achieves the effect of improving lubrication while maintaining the stability of the heat flow of the slag film. TiO2 can reduce viscosity and obtain good heat transfer performance while taking into account the lubrication of the ingot to improve the glass properties of the slag.
[0033] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A mold slag for continuous casting of high carbon steel slab, characterized in that: The invention comprises the following components in parts by weight: 15-50 parts of premelt, 10-30 parts of wollastonite, 3-10 parts of quartz, 3-8 parts of albite, 2-5 parts of magnesia, 2-4 parts of borax, 10-15 parts of soda ash, 1-3 parts of lithium carbonate, 1-2 parts of bentonite, 4-8 parts of graphite, 1-3 parts of adhesive, and 1-4 parts of isopropyl trioleyl titanate. The effective chemical components are as follows in percentage by mass: CaO: 22.5-30.5%, SiO2: 35.0-50.5%, MgO: 2-6.5%, Fe2O3: ≤2.0%, Al2O3: 3-7.15%, Na2O: 8-15.5%, Li2O: 0.3-1.5%, B2O3: 0.3-1.1%, TiO2: 0.1-1%, fixed carbon: 3.0-6.0%, and the rest are unavoidable impurities.
2. The mold slag for continuous casting of high carbon steel slab according to claim 1, characterized in that: The premelt is prepared by adding soda ash, limestone, albite, dolomite and coke into a premelting furnace and burning to obtain a liquid material, which is then cooled by cold water. The chemical composition is detected to be CaO: 35-36%, SiO2: 32-35%, Al2O3≤3.0%, MgO≤3.0%, MnO≤1.0%, Na2O: 7-8%, and the rest are inevitable impurities.
3. The mold slag for continuous casting of high carbon steel slab according to claim 1, characterized in that: The protective slag has a basicity of 0.65-1.0, a melting point of 950-1100° C., a melting speed of 15-35 s, and a viscosity of 0.1-0.3 Pa·s at 1300° C.
4. The mold slag for continuous casting of high carbon steel slab according to claim 1, characterized in that: The adhesive is prepared by mixing sodium carboxymethyl cellulose and yellow dextrin in a mass ratio of (1-3): (2-4).
5. A method for preparing mold slag for continuous casting of high carbon steel slab according to any one of claims 1 to 4, characterized in that: The steps include: S1. Weigh each component in the formula according to the proportion and stir evenly to obtain a mixture, add water to make a slurry, and then stir and grind to obtain a slurry; S2. The slurry is filtered, spray granulated and then sieved to obtain the product.
6. The method for preparing mold slag for continuous casting of high carbon steel slab according to claim 5, characterized in that: The slurry concentration is 55-65wt%.
7. The method for preparing mold slag for continuous casting of high carbon steel slab according to claim 5, characterized in that: The grinding time is 60 to 90 minutes.
8. The method for preparing mold slag for continuous casting of high carbon steel slab according to claim 5, characterized in that: The conditions for the spray granulation are a tower temperature of 650-750°C and a tower outlet temperature of 160-180°C.
9. The method for preparing mold slag for continuous casting of high carbon steel slab according to claim 5, characterized in that: The pump pressure for spray granulation is 1.3~2.3MPa.
10. The method for preparing mold slag for continuous casting of high carbon steel slab according to claim 5, characterized in that: The screening screen is a double-layer screen with 18 mesh on the upper layer and 60 mesh on the lower layer.
Citation Information
Patent Citations
Low fluorine casting powder containing boron for medium carbon steel and preparation process
CN103722142A
Casting powder for high-pulling-speed continuous casting of high-carbon steel square billet as well as preparation method and application of casting powder
CN117206481A
Fluorine-free environment-friendly type continuous casting protecting slag for the blast furnace slag containing titanium and the manufacturing process of the same
CN1481954A
Improvements relating to ceramic compositions
GB599806A
Synthetic calcium silicate and mold powder for continuous casting of steel using the same
JP2000169136A
Cited By
Crystallizer casting powder for continuous casting of wide and thick plate high-carbon steel and preparation method of crystallizer casting powder
CN120533033A